Pengaruh Penggunaan Abu-Sekam Padi sebagai Bahan Tambahan Terhadap Kuat Tekan Beton - Muhammad Farhan; Muhammad Nuklirullah; Fetty Febriasti Bahar (Universitas Negeri Gorontalo, 2023)
Concrete in its use as a construction material continues to increase and is increasingly widespread. The high level of use of concrete is caused by the many advantages offered by the use of concrete. Additives in concrete are one of the materials in concrete that can be innovated to obtain concrete characteristics and specifications. Additive material used in this research is rice husk ash. Rice husk ash used as an additive in this study was rice husk ash waste from Kerinci Regency. This research was conducted.with the aim of knowing how the use of rice husk ash as an additive can affect the compressive strength of concrete. The concrete used is cylindrical concrete with a concrete design quality of fc' 20 MPa. This research was conducted by experimental method. The results of the study with variations in the addition of rice husk ash to concrete as much as 0%, 6%, 8%, 10%, and 12% to the weight of cement obtained an optimum compressive strength value of 29.32 MPa. Laboratory tests on the compressive strength of concrete proved that the compressive strength.of concrete increased linearly with the addition of 6%, 8% and 10% rice husk ash.